Numerical and experimental preliminary study of temperature distribution in an electric resistance tube furnace for hot compression tests (2014)
Hot compression tests are performed when jaws, each one with a jacketed section to cool a part of its length, move through a tube furnace at elevated temperatures to compress a metal sample between them, changing the boundary conditions and the temperature distribution inside the furnace during the test. This paper presents a preliminary study about the variation of temperature inside a furnace for hot compression tests, when the jaws are positioned inside it. It also proposes a theoretical simulation to determine the temperature profile in the furnace, which is compared with experimental measurements. Both experimental measurement and simulation showed that the temperature inside the tube furnace for hot compression tests is not uniform. By comparing the simulated values with experimental measurements, it can be concluded that the simulation proposed in this paper is a useful tool which estimates the temperature inside a tube furnace in hot compression tests with an acceptable approximation (error less than 4.73%).